PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP EARNING RESPONSE COEFFICIENT ( Studi Pada Perusahaan-Perusahaan Sektor Jasa di BEI) - Aam Aminah; Sekar Mayangsari (Media Riset Akuntansi, Auditing & Informasi, 2011)
In their investment decision making process, investors need companies information to make any decision regarding their investment. Mostly, they only have the financial information. The using of the non financial information regarding social aspect which is popularly known as Corporate Social Responsibility (CSR) also can be used as additional information for the investment decision making.The purpose of the study is to examine the effect of the information of Corporate Social Responsibility disclosed in the companies' annual reports on the Earning Response Coefficient (ERC). Analytical tool for the study is regression analysis OLS cross sectional with Ridge Regression model. The sample of the study consist of 38 annual reports 2008 and 2009 of the companies in telecomunications, banking and financial services and transportation business listed at the Jakarta Stock Exchange (BEI). The result of the study by using ridge regression show that there is no effect between CSR disclosures on ERC eventhough the study has already using BETA, PBV and Leverage variables. CSR disclosures didn't have any effect on ERC. Investors still have no confidence on any social information provided annualy by the companies for their investment decision making. Also CSR disclosures in services business still be assumed as less important compared to the disclosures in mining or manufactured business.Based on the result of the study, for the further study we suggest as follows: (1) the addition of sectors besides services business, adding more samples, and the extension of exposure period (2) Adding additional variables that can influence the ERC (3) Giving more weight on the disclosure detail level and its measurement must be follow any international development on CSR (such as Global Reporting Initiatives) that should be suited with Indonesian' condition.